Traits of personality and development of the creativity - López Martínez, Olivia; Navarro Lozano, Juan (Anales de Psicología / Annals of Psychology, 2010)
The human being is the most important element in creativity. Besides, one of the most recurrent objectives in the research of creativity has been the identification of psychological traits - either intellectual or personality ones- that characterize creative people. The goal of the present work is to explore whether there are personality traits that make a signifi-cant impact on the development of creativity. With that aim in mind, we used a sample of 90 students from a Pre-school and Primary Education School: from the Altiplano area (Jumilla) in the Autonomous Region of Murcia (Spain). Our objectives and the hypothesis posed, as well as the characteristics of the selected sample, lead us to a quasi-experimental methodology, where there will be an experimental group and a control group equivalent to the first one. The results show that the rise in creativ-ity -obtained by applying a programme to improve creativity- is signifi-cantly related to some personality traits such as extraversion and anxiety.